APPLICATION OF INQUIRY LEARNING MODEL TO IMPROVE SOCIAL STUDIES LEARNING OUTCOMES OF GRADE III STUDENTS AT SD NEGERI BERINGIN JAYA - Cindy Septiana (Teaching and General Education Studies, 2025)
This study aims to determine the effectiveness of the inquiry learning model in improving social studies learning outcomes of grade III students of SD Negeri Beringin Jaya. The background of this research is based on the low social studies learning outcomes of students as shown by pre-test data and preliminary observations that show the lack of active participation of students in the learning process. The conventional teacher-centered learning model is one of the main causes of these low learning outcomes. For this reason, an approach is needed that is able to increase students' activeness, creativity, and understanding of social studies materials, one of which is through the application of the inquiry learning model. This study uses a quantitative approach with a quasi-experimental method and a one-group pretest-posttest design. The research subjects consisted of 20 grade III students of SD Negeri Beringin Jaya. The instrument used was a learning outcome test in the form of multiple choice as many as 20 questions. The validity and reliability of the instrument are tested before use. Data were analyzed using paired t-tests with a significance level of 0.05. The results of the study showed an increase in student learning outcomes after the implementation of the inquiry learning model. The average post-test score reached 79.6 compared to the pre-test of 57.5. The t-test yielded a t-count value of 7.8 with a significance of 0.002 (p < 0.05), indicating that there was a significant difference between before and after treatment. In conclusion, the inquiry learning model is effectively used to improve social studies learning outcomes in elementary school students.